(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the efficacy of long-course neoadjuvant chemoradiotherapy in patients with stage II–III low rectal cancer treated at 108 Military Central Hospital. Subjects and methods: A retrospective descriptive study was conducted on 83 patients with stage II–III low rectal cancer who received long-course neoadjuvant chemoradiotherapy at 108 Military Central Hospital from August 2018 to August 2023. Results: Tumor size decreased from 5.17 ± 1.90 cm to 3.96 ± 1.94 cm (p < 0.001). The proportion of tumors staged as T3–4 on MRI decreased from 95.2% to 62.7%. The rate of regional lymph node positivity on MRI decreased from 94.0% to 67.5% (p < 0.001). The proportion of patients with CEA > 5 ng/mL decreased from 48.2% to 10.8%. Overall, 97.6% of patients completed the chemoradiotherapy regimen as planned. On post-treatment MRI, mrTRG 1–3 accounted for 77.1%. The rates of pathological response were 22.9% for complete response (TRG 1), 16.9% for TRG 2, 43.4% for TRG 3, 12.0% for TRG 4, and 4.8% for TRG 5. Conclusion: Long-course preoperative chemoradiotherapy in patients with lower-third rectal cancer is a safe and effective treatment modality. It contributes to tumor downsizing, downstaging of mural invasion, reduction in MRI-detected lymph node involvement, decreased CEA levels, and a high rate of favorable histopathological response.